Elucidating the effects of individual components in KxMnOy/SiO2 and water on selectivity enhancement in the oxidative coupling of methane. Issue 17 (25th July 2021) - Aydin, Zeynep; Zanina, Anna; Kondratenko, Vita A.; Eckelt, Reinhard; Bartling, Stephan; Lund, Henrik; Rockstroh, Nils; Kreyenschulte, Carsten R.; Linke, David; Kondratenko, Evgenii V.
Abstract : To date, a great number of various materials have been tested for the oxidative coupling of methane (OCM). Abstract : To date, a great number of various materials have been tested for the oxidative coupling of methane (OCM). On the basis of previous statistical analysis of OCM-related literature data, we developed novel catalysts based on K2 MnO4 or KMnO4 supported on SiO2 showing selectivity to C2 -hydrocarbons (C2 H4 and C2 H6 ) up to 68 or 66%. The analysis of catalysts containing the single components (Mn/SiO2, K2 O/SiO2 or SiO2 ) demonstrates that the co-existence of K and Mn is essential for achieving high selectivity to the desired products. The selectivity can be additionally improved when the OCM reaction is performed in the presence of water. The positive effect of water is attributed to the suppressed direct oxidation of CH4 to CO2 . Water also enhances the rates of methane conversion into C2 -hydrocarbons and CO. Besides, the effects of water are more pronounced for samples based on crystalline SiO2 rather than amorphous SiO2 . Transient experiments with isotopically labelled oxygen suggest that the accelerating effect should be of heterogenous nature. As the positive influence of water on the selective methane oxidation to C2 -hydrocarbons has been established over different catalysts, it may be advantageous to consider it when developing novel materials for the OCM reaction and even for other oxidation reactions.